Effect of flow diversion for irrigation on peak rates of runoff from watersheds in and near the Rocky Mountain foothills of Colorado - Schleusener, Richard A., author; Smith, George L., author; Chen, Mingcheng, author; International Association of Hydrologists, publisher (Colorado State University. Libraries, 1962)
An investigation was made to determine the effect of flow diversions for irrigation on the magnitude and frequency of peak rates of runoff from selected small watersheds in the Rocky Mountain Foothills in Colorado. A study of seven watersheds smaller than 1,000 square miles indicates that the effect of flow diversion on peak rates of runoff is probably negligible for those watersheds for which peak rates of runoff are caused by rainstorms. Evidence indicates that flow diversions probably become significant for watersheds of 1,000 square miles or more for which snowmelt is a significant contributing factor in producing peak rates of flow.
CER60RAS36.
From Bulletin of the International Association of Scientific Hydrology, 1962.
Keywords: Runoff; Runoff -- Colorado; Irrigation -- Effect of runoff on; Irrigation -- Colorado